Estudio de la dinámica poblacional de (Bactericera Cockerelli) en dos sistemas de producción del tomate de arbol (Solanum Betaceum). - Álvarez Ureta, Carlos Alfredo (2023)
The current research was made into two locations, under controlled conditions in the Salache and Cusubamba Sector that it was determined the insect (Bactericera cockerelli) behavior, responsible for the phytoplasma transmission known as purple tip in the tree tomato crop. Within this investigative work, it was used a descriptive design, which consisted of studying and observing the B cockerelli incidence as they affect the crop in the Solanaceae family. During the process, it was observed insect development and was reported high damage rates at each stage. The recorded data, throughout the process were: eggs deposited number, development time each nymphal stage and the adult stage. The observation was made with weekly monitoring, keeping a plague incidence record, so it was used a manual use microscope adapted to a mobile device, in order to be able to observe with a 40x rapprochement, what allowed to visualize more closely, during the January to June 2022 months, which they were recorded the B cockerelli data, managing to determine, what the Cusubamba town had an oval development more quickly, since this was a conventional crop system, while in the Salache town had with an organic production system.